2019
DOI: 10.1051/0004-6361/201833163
|View full text |Cite
|
Sign up to set email alerts
|

Red-skewed Kα iron lines in GX 13+1

Abstract: Context. Broad, asymmetric, and red-skewed Fe K α emission lines have been observed in the spectra of low-mass X-ray binaries hosting neutron stars (NSs) as a compact object. Because more than one model is able to describe these features, the explanation of where and how the red-skewed Fe lines are produced is still a matter of discussion. It is broadly accepted that the shape of the Fe K α line is strongly determined by the special and general relativistic effects occurring in the innermost part of the accret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
7
1
Order By: Relevance
“…When we fitted the narrow residuals with Gaussian emission lines (Model 2), we found that the relativistic Fe-line complex could only be explained if the source inclination was low, i ࣠ 30 • . A low inclination is inconsistent with previous spectral results obtained with other instruments with better energy resolution than NuSTAR (D íaz Trigo et al 2012 ;Maiolino et al 2019 ). Additionally, a high inclination is necessary to explain the presence of dips in the light curves of GX 13 + 1 (Iaria et al 2014 ).…”
Section: Emission or Absorption Lines And Photoionizationcontrasting
confidence: 79%
See 3 more Smart Citations
“…When we fitted the narrow residuals with Gaussian emission lines (Model 2), we found that the relativistic Fe-line complex could only be explained if the source inclination was low, i ࣠ 30 • . A low inclination is inconsistent with previous spectral results obtained with other instruments with better energy resolution than NuSTAR (D íaz Trigo et al 2012 ;Maiolino et al 2019 ). Additionally, a high inclination is necessary to explain the presence of dips in the light curves of GX 13 + 1 (Iaria et al 2014 ).…”
Section: Emission or Absorption Lines And Photoionizationcontrasting
confidence: 79%
“…In Model 3, we considered a similar continuum model as Model 2, but we used multiplicative Gaussian absorption profiles, gabs , to fit MNRAS 522, 3367-3377 (2023) the narrow residuals that we identified as Fe XXVI K α at ∼6.7 keV, and either Ni XXVII and/or Ni XXVIII at ∼8 keV. Interestingly, our best-fitting Model 3 yielded an inclination of approximately ∼70 • , consistent with previous observations (D íaz Trigo et al 2012 ;Maiolino et al 2019 ).…”
Section: Emission or Absorption Lines And Photoionizationsupporting
confidence: 78%
See 2 more Smart Citations
“…On the other hand, they noticed that spectral features expected by the reflection scenario such as the K α fluorescent lines are either very weak or not observed during the outburst state in U Gem. It is important to stress, however, that reflection scenario is not the only one capable to explain the K α fluorescent line production (see, e.g., Maiolino et al 2019). Mukai et al (2003) showed that the Chandra spectrum of the DN U Gem (as well as SS Cyg and V603 Aql) can be described by the multi-temperature bremsstrahlung cooling-flow model mkcflow with kT max = 20 keV.…”
Section: U Gemmentioning
confidence: 99%